Ectopic Posterior Pituitary Lobe and Periventricular Heterotopia: Cerebral Malformations with the Same Underlying Mechanism? - Mitchell, L. Anne; Thomas, Paul Q.; Zacharin, Margaret R.; Scheffer, Ingrid E. (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Ectopic posterior pituitary lobe often occurs in children with growth hormone deficiency and is part of the spectrum associated with septo-optic dysplasia. Some cases of septo-optic dysplasia are caused by homozygous mutations in the homeobox gene HESX1, whereas heterozygous mutations are associated with milder phenotypes. To date, HESX1 is the only gene associated with ectopic posterior pituitary lobe. We describe an association between ectopic posterior pituitary lobe and periventricular heterotopia in four children without classic features of septo-optic dysplasia and suggest possible mechanisms on the basis of a review of pituitary embryology and recent molecular genetic advances.METHODS: Among 20 children with ectopic posterior pituitary lobe, four had associated periventricular heterotopia. We herein review the clinical and MR imaging findings of these four children. Mutation screening of HESX1 was performed in two.RESULTS: All four children had growth hormone deficiency. None had visual or neurologic disturbances. MR images showed a range of pituitary appearances, with scattered discrete periventricular heterotopia in each case. Other abnormalities were limited to small suprasellar lipomas and callosal dysgenesis. A heterozygous HESX1 mutation was present in one case.CONCLUSION: The coexistence of ectopic posterior pituitary lobe and periventricular heterotopia suggests they have a common underlying genetic basis that is due to gene expression at different locations and stages of development. The presence of a heterozygous HESX1 mutation in one case suggests this gene is important in the development of both ectopic posterior pituitary lobe and periventricular heterotopia and supports their place in the spectrum of septo-optic dysplasia. Further analysis of HESX1 and other genes in related developmental pathways will elucidate their roles in the development of both malformations.